2021
DOI: 10.1038/s41598-020-80497-6
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo model allowing continuous observation of human vascular formation in the same animal over time

Abstract: Angiogenesis contributes to numerous pathological conditions. Understanding the molecular mechanisms of angiogenesis will offer new therapeutic opportunities. Several experimental in vivo models that better represent the pathological conditions have been generated for this purpose in mice, but it is difficult to translate results from mouse to human blood vessels. To understand human vascular biology and translate findings into human research, we need human blood vessel models to replicate human vascular physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Song et al found differences between mouse and human brain vasculature, that might be crucial for drug delivery and disease [70]. Interestingly, emerging approaches to address this limitation include an in vivo human blood vessel transplantation model [71].…”
mentioning
confidence: 99%
“…Song et al found differences between mouse and human brain vasculature, that might be crucial for drug delivery and disease [70]. Interestingly, emerging approaches to address this limitation include an in vivo human blood vessel transplantation model [71].…”
mentioning
confidence: 99%
“…In vivo visualization of transplanted vessels was performed with a TCS/SP8 confocal microscope (Leica Microsystems, Wetzlar, Germany) equipped with a Chamelon laser (Coherent, Santa Clara, CA, USA) as previously reported 49 . During imaging, an animal’s head was immobilized using a custom-made cranial window holder.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a recent development involves a flexible and sutureless silicon window that enables visualization of muscle tissue and orthotopic breast cancer 106 . Bone windows have been created for imaging brain tumor vasculature 107 and bone marrow 108 , 109 . The cranial window 107 is mainly used for cerebral vessel imaging while the femur window 110 , 111 is used for bone marrow imaging.…”
Section: Methods To Visualize Vasculature In Vivomentioning
confidence: 99%